A moderate Buddhist animal research ethics. Issue 2 (21st February 2019) - Fenton, Andrew
Abstract: Though there is a burgeoning interest in applied Buddhist ethics, Buddhist animal research ethics remains an underdeveloped area. In this paper I will explore how some central Buddhist ethical considerations can usefully engage our use of other animals (henceforth, animals) in science. As the scientific use of animals is broad, I will narrow my focus to laboratory science. I will show that, though a Buddhist abolitionism would not be unmotivated, it is possible to reject it. While doing so, it will be important to resist emphasizing elements of Buddhist thought that merely provide reasons to adopt the dominant ethical framework governing laboratory animal research ethics, known as the 3Rs. Though I will suggest how a Buddhist animal research ethics can sometimes permit the use of animals in harmful research, it will also require ethical constraints that resonate with some of the more progressive elements in 'Western' bioethics.